Crosniera wennerae, a new species of thalassinidean (Crustacea: Decapoda: Thomassiniidae) from the South Atlantic Bight - Heard, Richard W.; King, Rachael A. (Zootaxa, 2007)
Crosniera wennerae sp. nov. is described from a depth of 318 m in the South Atlantic Bight off North Carolina, USA. The species, based on a female specimen 20 mm in length, is distinguished from the other four nominal species of the genus by a combination of characters, including smooth uropodal lateral margins, well-developed exopods on maxillipeds 2 and 3, the smooth inner margin of the merus of maxilliped 3, and the presence of long, simple setae on the uropods, telson, and posterior margin of sixth abdominal somite. Crosniera wennerae sp. nov. represents the second member of the genus described from the western Atlantic. A key is presented for the separation of the species of Crosniera.